Strength properties of fly ash based geopolymer concrete containing bottom ash - Dehghan Najmabadi, Alireza (2012)
The most important purpose of this research is concerning about the environment. Each year, vast amounts of natural resources are consumed to manufacture ordinary Portland cement which itself causes considerable environmental problems. Geopolymer can be considered as the key factor which does not utilize Portland cement, nor releases greenhouse gases. Sufficient data is available about researches on fly ash based geopolymer concrete, but using both fly ash and bottom ash has a new era. Bottom ash is another waste from the process of combustion of coal and was used as partial replacement of sand in fly ash based geopolymer concrete and the ideal percentage of this replacement was one of the aims of this project. To find 7, 14 and 28 days compressive strength, three 100×100×100mm specimens with 0, 20, 40 and 60 percent replacement of bottom ash were prepared and cured at ambient condition (28oC). Same condition of curing was provided for 200×100mm cylinder specimens to determine 7-day and 28-day tensile strength and 100×100×500mm prisms were tested to find flexural strength at 7-day and 28-day of the four mixtures. Sodium silicate (Na2SiO3) and sodium hydroxide (NaOH) solution 14M with ratio of 2.5 were used as alkaline activator and all other parameters were kept constant to ignore other unknown influences. The optimum rate of replacement was 20% which produced geopolymer concrete with 28-day compressive strength of 26.5MPa, tensile strength of 2.81MPa and flexural strength of 4.30MPa.